2005
DOI: 10.1063/1.2102901
|View full text |Cite
|
Sign up to set email alerts
|

A theory of transport properties in molten salts

Abstract: Expressions for diffusion constants in molten salts have been obtained in terms of the inter-ionic pair potentials and the pair distribution functions. Numerical attempts for diffusion constants in molten alkali halides are carried out and results agreed fairly with those obtained by molecular-dynamics simulation and with some experimental data. Based on the coupling of generalized Langevin equation and damped Einstein oscillator equation, ions' velocity autocorrelation functions have also been described and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…The equations of partial conductivities for cation and anion, σ + and σ − , and the diffusion constants, D + and D − , in binary molten salts were already derived in the pervious work on the basis of the linear response theory [14]. In accordance with these results, we have…”
Section: Deviation From Nernst-einstein Relationsupporting
confidence: 77%
See 1 more Smart Citation
“…The equations of partial conductivities for cation and anion, σ + and σ − , and the diffusion constants, D + and D − , in binary molten salts were already derived in the pervious work on the basis of the linear response theory [14]. In accordance with these results, we have…”
Section: Deviation From Nernst-einstein Relationsupporting
confidence: 77%
“…In this calculation, we will use the first maximum position of g +− (r) as the distance of ion's contact. The quantity Δ BR was obtained by Berne and Rice [15], though recently certified by present authors in a different way [14]. Δ BR is essentially caused by an asymmetric distribution of the surrounded ions around the centered ion under an applied external field.…”
Section: Deviation From Nernst-einstein Relationmentioning
confidence: 99%
“…In order to study the structural and transport properties in molten salts, experimental investigations and molecular dynamics simulations have also been carried out from mid 70s of the last century [7][8][9][10][11]. Following these studies, we have been recently engaged in the study of transport properties in molten salts [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The partial conductivities for cation and anion, σ + and σ -, and the diffusion constants D + and D -were already derived before (Koishi & Tamaki, 2005). Taking these results, we have…”
Section: Deviation From Nernst-einstein Relationmentioning
confidence: 78%
“…Here, we will use the first maximum position of ɡ+-(r) as the distance of ionic contact. The quantity Δ BR is essentially caused by an asymmetric distribution of the surrounded ions around the centered ion under an applied external field; it was obtained by Berne and Rice (Berne & Rice, 1964), and recently certified by the present authors in a different way (Koishi & Tamaki, 2005). Since it was found that values of α 0 , α + and α -are numerically close to one another, we can take Δ~Δ BR as the deviation from Nernst-Eistein relation in a molten salt.…”
Section: Deviation From Nernst-einstein Relationmentioning
confidence: 99%